Bridging Landscape-Level Insights and Plot-Scale Actions through a Natural Resource Management Tool - Reddy, Nagarjuna N.; Garg, Kaushal K.; Singh, Ramesh (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Agricultural decision-making often faces challenges due to fragmented data and limited access to field-specific information. Farmers and resource managers frequently make critical choices without a holistic understanding of landscape characteristics and resource availability. To overcome this limitation, a digital decision dashboard is being developed to integrate landscape-level datasets with plot-scale decision support. This platform brings together multiple layers of information such as soil properties, land use, land slope, and infrastructure on a single interface to enable informed, site-specific, and resource-efficient decisions. The system begins by collecting a limited number of soil samples from representative locations within the landscape. These samples are analyzed to generate key soil parameters such as texture, nutrient content, and organic matter. Using digital soil mapping by incorporating topographical variability, biophysical factors, and land use patterns, a high-resolution digital soil maps is generated, enabling nutrient status estimation for unsampled fields. With this generated spatial database, fertilizer recommendations can be customized for each field parcel, aligning with balanced nutrient management principles for different cropping systems. A similar framework is applied for water resource assessment, where freshwater availability is estimated at field level. Based on this information, suitable cropping systems are being recommended that match water availability, soil conditions, and infrastructure. This integrated decision-making framework bridges critical data gaps between primary field measurements and secondary information sources, generating actionable intelligence at farm scale. The dashboard allows users to visualize, analyze, and select suitable interventions from a range of options, thereby supporting sustainable and profitable resource use. By combining spatial data analytics with practical field-level recommendations, this platform empowers farmers, extension workers, and policymakers to adopt climate-resilient and resource-efficient strategies. The digital decision dashboard will contribute to enhancing productivity, improving water and nutrient use efficiency, and advancing the goals of precision and sustainable agriculture at scale.